Pengaruh Rasio Likuiditas,Rasio Profitabilitas dan Rasio Pasar terhadap Return Saham Pada Perusahaan Yang Tergabung Dalam Indeks LQ 45 Di Bursa Efek Indonesia - Siska, Noviarma; Agusti, Restu; Basri, Yesi Mutia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The liquidity ratio is used to measure the company's ability to meet obligations to parties outside the company or within the company that have matured. If the company is able to meet its obligations, the company said in a liquid state. Current Ratio (CR) is a ratio to measure a company's ability to pay short-term obligations or debt immediately due at the time billed as a whole .The ratio is the ratio of profitability to assess the ability of the company to make a profit. The results of these measurements can be used as an evaluation of the performance of management, whether they are working effectively or not. Return on Assets is a measure of a company's ability to generate profits with all the assets owned by the company (Kasmir 2008). Return on equity is a financial analysis tool for measuring profitability. This ratio measures the company's ability to generate profits based on certain capital. Return on equity is a profitability measure from the point of view of shareholdersMarket ratio is a ratio that is often used in special and capital markets that describes a situation or state of the company's achievements capital market (Harahap, 2004). Price Earning Ratio (PER) is a way of measuring how much investors assess corporate profits generated. Darmadji and Fakhrudin (2006) Price Earning Ratio (PER) describe the market appreciation of the company's ability to generate profits. Price Book Value (PBV) is a ratio used to measure the market performance of the stock market price of the book value (Ang, 1997). According Ratnasari (2003) Value Price Book Value (PBV) which indicates greater market price of such shares higher as well.Keyword : Stock Returns